Vertigo, poetry and creed of Alfred Hitchcock's cinema - Rafael J. Pascual (FahrenHouse, 2011)
In this article we analyse the film Vertigo -undoubtedly one of the North-American film di- rector Alfred Hitchcock's masterpiece- as an audiovisual poem we could identify with such a characteristic and defining name as film-poetry. We will try to show some elements very typical of cinema -the use of the light, colour, and music, the aesthetic treatment of image and the camera movement- they all aspects that in- fluence -as well as does plot- the rhythm, form and content in the same way as a poem does, in order to place cinema at the same level as poetry. We will try to describe in a very essential way the relations between cinema and arts such as music, painting and literature.